HUBUNGAN KUALITAS TIDUR DENGAN TINGKAT CANCER-RELATED FATIGUE (CRF) PADA PASIEN KANKER PAYUDARA PASCA KEMOTERAPI - Mulyana Utami, Luh Made Ayurda Prabhunjati; Nurhesti, Putu Oka Yuli; Utami, Kadek Cahya (Coping: Community of Publishing in Nursing; Vol 12 No 3 (2024): Juni 2024, 2024)
Breast cancer patients undergoing chemotherapy often experience increased fatigue. Cancer-related fatigue (CRF) is a subjective sensation of physical, emotional, and cognitive fatigue related to cancer or its treatment, which can interfere with normal activities and typically lasts more than six months. One of the factors contributing to CRF is sleep quality. This study aims to determine the relationship between sleep quality and CRF levels in breast cancer patients post-chemotherapy. This research is a quantitative study with a cross-sectional design conducted over three months from February to May 2024. The sampling technique used in this study was purposive sampling (n=30). Data are collected using the Pittsburgh Sleep Quality Index (PSQI) and Multidimensional Fatigue Inventory-20 (MFI-20). The study results, analyzed using the Spearman rank test, show a p-value of <0.001 and an r-value of 0.757, indicating a positive relationship between sleep quality and CRF levels in breast cancer patients post-chemotherapy. The worse the sleep quality, the higher the CRF level in patients. Breast cancer patients are expected to recognize the impact of poor sleep quality on CRF.